Immigrant Women and Labour Flexibility: Resisting Training through Learning - Shahrzad Mojab; Roxana Ng; Kiran Mirchandani (Adult Education Research Conference, 2000)
This research roundtable focuses on the lives and experiences of immigrant women in the context of the casualisation of labour and job deskilling. The presenters document the failure of training programs to challenge the ghettoisation of immigrant women in contingent and peripheral jobs and focus on the ways in which women learn to resist racialized and gendered exclusion in state approaches to training.